Competition system of elite cross-country sprint skiers during the preparation for and participation in the XXIV Olympic Winter Games 2022 in Beijing (PRC) - Dubrovinskiy, S.S.; Batalov, A.G. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyse the competition system of elite cross-country skiers at the stage of direct preparation for the Olympic Winter Games (OWG) 2022 in Beijing. Methods and structure of the study. The factual material of the study was obtained through the analysis of the competition systems of the winners and medallists of the OWG 2022 at the World Cup (WC) stages in 2021/22. The characteristic features of the construction of such systems include the following: the total number of starts in the WC before the beginning of the OWG; the distribution of starts across WC periods; the ratio of starts in various competitive disciplines in the classical and free styles and their performance outcomes; participation in the multi-day WC tournament – Tour de Ski (8 starts over 10 days). The primary informational and documentary source was the materials of the official FIS website. Results and conclusions. Sprint competitions at the 2022 Olympic Winter Games in Beijing were held in the free style on a ski course of 1,461 m for both men and women. Based on the results of the performances of cross-country skiers at the OWG 2022, it was noted that out of 6 possible medals awarded in the individual sprint, five medals were won by representatives of different countries: Sweden, Russia, the USA, Norway and Italy – which indicates a high level of competition in this discipline.